Dominant Factors Influencing Students' Decisions to Pursue Master of Elementary Education Programs: An Exploratory Study - Resna Amalia; Sumanti Sumanti; Siti Aisyah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
The growing demand for postgraduate education in Indonesia has prompted increasing interest in master's programs, including those in elementary education. However, empirical evidence on the factors that motivate students to pursue these programs remains limited, particularly in private universities. This study aimed to identify and analyze the dominant factors influencing students' decisions to enroll in the Master of Elementary Education Program at the Postgraduate Program of Universitas Adzkia. A quantitative survey design was employed, involving 80 students selected through purposive sampling. Data were collected using a validated questionnaire and analyzed through Exploratory Factor Analysis (EFA). The results revealed five dominant factors that cumulatively explained 63.7% of the total variance: academic quality (18.34%), career advancement (13.91%), institutional reputation (9.17%), personal motivation (7.57%), and financial considerations (5.46%). Among these, academic quality and career advancement emerged as the most influential determinants, indicating that students weigh both academic excellence and professional relevance when making graduate enrollment decisions. These findings suggest that graduate programs must prioritize academic excellence and career relevance to attract prospective students effectively.